Burnout syndrome in young school-age athletes - Velasque, Leonardo Dummer (2023)
The purpose of the present work is to identify the prevalence of Burnout Syndrome in young athletes of school age. This work is a descriptive cross-sectional study with quantitative characteristics, with a sample consisting of 24 young men, between 15 and 17 years of age, from a youth football category. The “Athlete Burnout Questionnaire” was used, consisting of 15 multiple-choice questions, using the five-point Likert scale. Data normality was tested using the Shapiro-Wilk test. The descriptive results of the questions were described by means of median and interquartile range (25 – 75). As for the data on dimensions, parametric statistics were used, presenting these results in mean and standard deviation. The question with the highest median (4) was “Am I accomplishing many worthwhile things in sport?”. It was still possible to identify that the dimension that had a different result from the others was “physical and emotional exhaustion”, with a median of 2. All statistical treatment was performed using SPSS 20.0 software. It was identified that the athletes involved do not present Burnout syndrome characteristics, considering the criteria previously established by the scientific literature.